Vaccination and sport: a systematic review - Tafuri, S.; Stefanizzi, P.; Riformato, G.; Cuscianna, E.; Rizzi, D.; Bianchi, F. P. (Medicina dello Sport, 2023)
INTRODUCTION: Infectious diseases pose a significant risk to athletes, especially professional athletes, due to the nature of their training, travel, and close contact with other individuals. The athletic environment, characterized by crowded training facilities, shared equipment, and frequent exposure to large groups of people, can create a setting at increased risk for the transmission and spread of various infectious agents.